Revitalizing Zion: Nineteenth-Century Mormonism and Today’s Urban Sprawl (Utah Environmental Law Review, 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} In the nineteenth century, Mormons planned and built hundreds of communities throughout the West. Time, growth, and redevelopment have begun to erase this history. Like towns and cities across the country, places first settled by Mormons now grapple with urban sprawl’s challenges. This article explores whether the Mormons bold planning effort that permeated the frontier of the Old West of the nineteenth century has any lessons to offer those grappling with the planning challenges facing the New West of today.